Control of silver throwing power by pulse reverse electroplating. (2nd January 2017) - Leisner, P.; Zanella, C.; Belov, I.; Edström, C.; Sandulache, G.; Hansal, W. E. G.
Abstract : The influence of electroplating parameters on throwing power (TP) is studied in additive-free silver cyanide solutions under direct current and pulse reverse electroplating conditions. It is found that the best TP is obtained when no agitation of the electrolyte is applied. The most important parameters for controlling the TP are the cathodic current density, the anodic to cathodic charge ratio, and the ratio between the anodic and cathodic current densities. Guidelines for process optimisation are given.